Herbicidas para el control de Spermacoce L en papaya (Carica papaya) - Bogantes-Arias, A.=700 1 Hernandez-Chavez, M.; Mora-Newcomer, E.
(Es, En)
Ilus., 17 ref.
Keywords: CARICA PAPAYA; HIBRIDOS; MALEZAS; ESCARDA; HERBICIDAS; COSTA RICA; PREMERGENTES; POSTEMERGENTES; AGRONOMIA MESOAMERICANA